2017
DOI: 10.1021/acschemneuro.7b00284
|View full text |Cite
|
Sign up to set email alerts
|

Placement of Hydroxy Moiety on Pendant of Peptidomimetic Scaffold Modulates Mu and Kappa Opioid Receptor Efficacy

Abstract: In an effort to expand the structure–activity relationship (SAR) studies of a series of mixed-efficacy opioid ligands, peptidomimetics that incorporate methoxy and hydroxy groups around a benzyl or 2-methylindanyl pendant on a tetrahydroquinoline (THQ) core of the peptidomimetics were evaluated. Compounds containing a methoxy or hydroxy moiety in the o- or m-positions increased binding affinity to the kappa opioid receptor (KOR), whereas compounds containing methoxy or hydroxy groups in the p-position decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…previously in different studies. 17,24,38,43,44 For the same reason, (II) and (IV) were also included in this study as additional MOR and KOR reference compounds. It needs to be noted here that because different reference compounds for MOR and KOR had to be used, the comparability of the data is limited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…previously in different studies. 17,24,38,43,44 For the same reason, (II) and (IV) were also included in this study as additional MOR and KOR reference compounds. It needs to be noted here that because different reference compounds for MOR and KOR had to be used, the comparability of the data is limited.…”
Section: Resultsmentioning
confidence: 99%
“…15 Ligands, which are partial MOR agonists and full KOR agonists, are of interest for pharmaceutical research, since they probably have analgesic potential with a reduced risk of respiratory depression, tolerance, and abuse. 17 Other reported adverse effects resulting from recreational opioid consumption include hypothermia, sedation, anxiety, sweating, disorientation, drowsiness, nausea, obstipation, and miosis. 18,19 In 2009, the first NSO (o-desmethyltramadol) was reported to the EMCDDA Early Warning System.…”
Section: Introductionmentioning
confidence: 99%
“…Given the potential of these ligands to produce antinociception with reduced adverse effects, our lab has been developing a promising MOR-agonist/DOR-antagonist peptidomimetic series containing a tetrahydroquinoline (THQ) core. , As stability is an issue in this series, we recently reported an initial SAR study that showed it was possible to eliminate part of the tetrahydroquinoline core of these peptidomimetics and maintain the desired MOR-agonist/DOR-antagonist profile . While this approach proved useful for improving metabolic stability, we wished to enhance the potency and efficacy of these compounds at MOR and further increase their stability.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of our development of a MOR-agonist/DOR-antagonist peptidomimetic series with a reduced abuse profile, we found that the core tetrahydroquinoline structure in this series was a major metabolic liability. As such, we opted to simplify the core to a benzene ring .…”
Section: Introductionmentioning
confidence: 99%